Research on the order of compression and filtering in the digital signal processing - Yuan Yongsheng Meng Qingsheng (Tongxin xuebao)
This paper applies specified mathematical methods in researching the influence on the final errors of the order of compression and filtering. After considering the order, this paper presents two general expressions of the errors, and points out that under some special conditions they are equal if using diagonal Wiener filter. In addition, it has a example which help explain such a fact that the value of the expressions have been related to the filtering matrix and noise covariance matrix.